Shielding design of a target station and radiation dose level investigation of proton linac for a compact accelerator-driven neutron source applied at industrial sites. (July 2018) - Ma, Baolong; Otake, Yoshie; Wang, Sheng; Sunaga, Hideyuki; Yamagata, Yutaka; Taketani, Atsushi; Hu, Huasi; Jia, Qinggang; Hu, Guang; Bautista, Unico
Abstract: The shielding design for a compact accelerator-driven neutron source (CANS) that is applied in industries was studied using both theoretical simulations and experimental measurements. Neutron shielding material composition for CANS was optimized by coupling the genetic algorithm with the Monte Carlo code. A multi-layer shielding structure was developed and successfully applied to a CANS target station. The high radiation dose of CANS proton linac was investigated in detail on the basis of experimental measurements, and the radiation dose was significantly reduced by replacing the material of its bellow pipes. Highlights: Shielding material was optimized by GA algorithm coupled with Monte Carlo code. A multi-layer shielding structure was adopted and showed significant advantages. Materials of bellow for CANS proton linac were studied from a new perspective.